Proximate Composition of Anadara granosa and Paphia undulata - Permata, Yade Metri; Liesna, Anggi Tri; Rangkuti, Fahmi Muhammad; Insyra, Kharisma; Dayanti, Yasmin (Talenta Publisher, 2023)
The sea region of Indonesia is particularly abundant in natural resources. One of the economically viable aquatic commodities is shellfish. The public has a high demand for the shellfish Anadara granosa and Paphia undulata. The goal of this study was to ascertain the protein, carbohydrate, fat, water, and ash content of Anadara granosa and Paphia undulata. The study's sample was intentionally drawn from the sea waters off the coast of Belawan, North Sumatera. Following the SNI technique, the proximal level measurement method was used. According to the examination of proximate levels, there is a 10–12% protein content, 0.14–0.15% carbohydrate content, 1% lipid content, 70%–80% water content, and 2% ash content. It can be concluded that, as functional foods, Anadara granosa and Paphia undulata include nutrients that are good for your health.